Analyzing Organization Culture’s Role on Digital Transformation During Pandemic Era: An Ethnographic Study - Triani, Meidiana; Hasan, Djohan Gunawan; Susanto, Yosef Budi (International Journal Labs, 2023)
Public behavior toward shopping is changing due to limited mobility. E-commerce has changed consumer shopping behavior. The pandemic has accelerated the digital transformation process. From this, the company finally decided to carry out digital transformation and try to sell their product to e-commerce. The company uses digital marketing to market its brands effectively to the public during a pandemic. The application of digital transformation makes organizational culture an important thing that influences the success or failure of digital transformation. The culture in each company will make the strategy of each company different. Corporate culture has a role in measuring the company's success in implementing digital transformation to deal with the pandemic. Because of this, this study uses Hofstede's organizational culture theory and cultural dimension theory. Ethnography is the method in this research because researchers can focus on culture. In general, ethnography is for researchers who are outside the organization. However, in this study, researchers are part of an organization, so they have a more in-depth picture of the culture that occurs within it. From this study, the symbol in each category of organizational culture in the company has a unique meaning, which plays a role in digital transformation that will impact company performance. The combination of cultural dimensions is also a factor in the success of digital transformation in companies. Culture, organization, consumers, technology, and strategy are five things in digital transformation that affect company performance.